Variations in leaf temperature, plant internal resistance, photon requirement and transpiration of pigeonpea under bare and mulched soil conditions - CHOWDHURY, A.; DAS, H. P.; SAMUI, R. P.; SHEIKH, A. M. (MAUSAM, 1996)
ABSTRACT. The paper presents the results of an experiment conducted during 1992 and 1993 crop seasons at the farm of Gujarat Agricultural University, Anand on pigeonpea to determine variations in agro-meteorological characteristics of leaf transpiration leaf temperature plant diffusive resistance and quanta were considered at three levels within the crop canopy in mulched and unmulched fields. The anlilysis rewaled that leaf temperature is more in unmulched field where transpiration rates are lower than the mulched field. Stomatal resistance and the quantum requirements nearly match in both the treatments. Stomatal conductance attains large values in morning and evening hours.